1995
DOI: 10.1182/blood.v86.11.4337.bloodjournal86114337
|View full text |Cite
|
Sign up to set email alerts
|

CD8-depleted donor lymphocyte infusion as treatment for relapsed chronic myelogenous leukemia after allogeneic bone marrow transplantation

Abstract: Donor lymphocyte infusions can reinduce complete remission in the majority of patients with chronic myelogenous leukemia (CML) who relapse into chronic phase after allogeneic bone marrow transplantation (BMT). Such infusions are associated with a high incidence of graft- versus-host disease (GVHD) and marrow aplasia. BMT using selective depletion of CD8+ lymphocytes from donor cells reduces the incidence of GVHD without an increase in leukemia relapse. We hypothesized that infusion of CD8-depleted donor periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(58 citation statements)
references
References 27 publications
0
56
0
2
Order By: Relevance
“…2 Although DLI frequently results in significant acute and/ or chronic graft-versus-host disease (GVHD), several groups have demonstrated that depletion of CD8 T cells from DLIs efficiently reduces the incidence and severity of GVHD while maintaining GVL activity. 3,4 Therefore, selective CD4 DLI is expected to provide an effective and low-toxicity therapeutic strategy for improving post-transplant immune function. Actually, selective CD4 DLI based on a recently established method for ex vivo T-cell expansion using anti-CD3 monoclonal antibody and interleukin (IL)-2 is now becoming established as a routine therapeutic means of resolving posttransplant immunological problems in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although DLI frequently results in significant acute and/ or chronic graft-versus-host disease (GVHD), several groups have demonstrated that depletion of CD8 T cells from DLIs efficiently reduces the incidence and severity of GVHD while maintaining GVL activity. 3,4 Therefore, selective CD4 DLI is expected to provide an effective and low-toxicity therapeutic strategy for improving post-transplant immune function. Actually, selective CD4 DLI based on a recently established method for ex vivo T-cell expansion using anti-CD3 monoclonal antibody and interleukin (IL)-2 is now becoming established as a routine therapeutic means of resolving posttransplant immunological problems in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…22) In relapse patients with CML, approximately 82% and 73% of the allo-BMT recipients infused with donor-derived T cells have been reported to enter cytogenetic and molecular remission, respectively. 9,23) Clinical trials with DCs in treating tumor-bearing patients have achieved success, as has been the case in animal models. [24][25][26][27] DCs are antigen-presenting cells that can enhance the generation of antigen-specific helper and cytotoxic T cells from naive T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In one study CD4 + but not CD8 + T cell and NK cell numbers after BMT were higher in patients who did not relapse, and superior NK function was also associated with continued remission [30]. As previously mentioned, there is some evidence from CD8 + depletion of BMT and donor lymphocytes that CD4 + T cells are more important than CD8 + T cells in the GVL response to CML [27][28][29]. However, the conclusions that CD4 + cells are necessary and sufficient to confer GVL must be balanced against the possibility that the GVL effect is conferred by a small number of residual CD8 + T cells or accompanying NK cells in the transplant.…”
Section: Gvl Reactivity After Bmt and Dltmentioning
confidence: 95%